"A CHRONICLE OF FORENSIC SCIENCE AT THE TASHKENT MEDICAL ACADEMY: FROM FOUNDATIONS TO MODERN PRACTICE" (Modern education and development, 2025)
The article presents the stages of formation and development of the Department of Forensic Medicine and Medical Law of the Tashkent Medical Academy. Information is provided about the heads of the department at different periods of its activity, the composition of professors and teachers, and the training of highly qualified scientific and pedagogical personnel. The role of the department in training doctors and specialists for forensic examination services at the undergraduate level is especially emphasized.